Hard coating film and cutting tool using said hard coating film
By setting the alternate lamination structure and thickness of AlCrN and TiSiN layers in the hard coating, the problem of the reduction of hardness of AlCrN and TiSiN at high temperatures is solved, and the high performance and long life of the hard coating are achieved, and suitable for a wide range of processing conditions .
Patent Information
- Application Number
- CN202380034949.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-28
- Filing Date
- 2023-04-25
- Publication Date
- 2024-12-17
AI Technical Summary
The existing AlCrN and TiSiN hard coatings exhibit reduced hardness and strength at high temperatures, resulting in short life and poor performance of cutting tools under severe conditions.
By setting the AlCrN and TiSiN layers as specific compositions and laminated structures, an alternately laminated hard film is formed, ensuring that the thickness of the C layer is 7 nm or more and 18 nm or less, the thickness of the A and B layers is less than 10 nm, and in the C layer, it is in the C layer. Equalization includes layers A and B to form a super multilayer structure.
It realizes a stable and high-performance hard film under a wide range of processing conditions, with excellent wear resistance, heat resistance, defect resistance and film strength, and extends the life of the cutting tool.
Smart Images

Figure CN119156265A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a hard film and a cutting tool using the hard film. Background Art
[0002] Regarding cutting tools used for processing metal materials such as steel, since the cutting object is high in hardness, during cutting, a large impact is sometimes applied to the cutting tool, and a high temperature of more than 800° C. is applied. Therefore, in order to improve the wear resistance and heat resistance of the cutting tool, the surface of the cutting tool is usually coated.
[0003] The coating is performed by, for example, depositing nitrides of titanium, chromium, etc., on a substrate such as high-speed steel or superhard alloy to form a thin film. Various methods have been proposed so far to improve the wear resistance and the like.
[0004] For example, Patent Document 1 proposes a method including at least one (Al y Cr 1-y )X layers (0.2≦y≦0.7), and / or one (Ti z Si 1-z )X layer (0.01≦z≦0.3) of hard material layer, the hard material layer comprising at least one stack having the following structure: another (AlCrTiSi)X mixed layer followed by another (Ti z Si 1-z )X layer, followed by another (AlCrTiSi)X mixed layer, followed by another (Al y Cr 1-y )X layers. The X is, for example, N.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2013-176837 Summary of the invention
[0008] Problems to be solved by the invention
[0009] Patent Document 1 states that the Al in the hard material layer y Cr 1-y N layer and Ti z Si 1-z The optimum thickness of the N layer is necessary to improve the life (patent document 1,
[0016] ). y Cr 1-y The thickness of the N layer is 75nm to 200nm, preferably 120nm to 170nm.z Si 1-z The thickness of the N layer is 50 nm to 150 nm, and preferably 70 nm to 120 nm.
[0010] AlCrN and TiSiN are materials commonly used for coating cutting tools. AlCrN has the advantage of excellent defect resistance at low temperatures, but has the disadvantage of reduced hardness and strength due to N shedding at high temperatures. In addition, TiSiN has the advantages of excellent wear resistance and is suitable for high-speed cutting operations, but has the disadvantage of being hard and brittle. Therefore, a hard film containing AlCrN and TiSiN is required to have both the above advantages and not show the above disadvantages.
[0011] The hard material layer described in Patent Document 1 includes the mixed layer, and Al y Cr 1-y N layer and Ti z Si 1-z Since the N layer is thick, it is highly likely to show the average characteristics of AlCrN and TiSiN or to show any of the above-mentioned disadvantages. Therefore, from the perspective of stably exhibiting high performance under a wide range of processing conditions, the hard material layer has room for improvement.
[0012] In addition, other existing hard coatings also have the problem of exhibiting any of the disadvantages of AlCrN and TiSiN. Therefore, the cutting tools coated with the hard coatings have insufficient properties such as coating hardness, heat resistance, wear resistance, and defect resistance, and have a short life, especially under severe cutting conditions.
[0013] Therefore, an object of one embodiment of the present invention is to realize a hard film that has the advantages of both AlCrN and TiSiN and can stably exhibit high performance under a wide range of processing conditions, and a cutting tool using the hard film.
[0014] Technical means of solving problems
[0015] The inventors studied the composition and structure of a hard film that combines the advantages of AlCrN and TiSiN. As a result, they found that by setting AlCrN and TiSiN to specific compositions and setting the AlCrN layer and the TiSiN layer to a specific stacking structure, a hard film that stably exhibits high performance under a wide range of processing conditions can be achieved, and thus came up with the present invention.
[0016] In order to solve the above problem, a hard film according to an embodiment of the present invention includes Al x Cr 1-x The A layer of N and Ti 1-y Si yN B layers are alternately stacked, when a combination of the alternately stacked A layers and the B layers is set as the C layer, the thickness of the C layer is 7 nm or more and 18 nm or less, the total thickness of the C layer is 1 μm or more and 6 μm or less, and the thickness of the A layer and the B layer are less than 10 nm. (Here, x is 0.6 or more and 0.7 or less, and y is greater than 0.05 and less than 0.08)
[0017] Effects of the Invention
[0018] According to one embodiment of the present invention, a hard film having advantages of both AlCrN and TiSiN and stably exhibiting high performance under a wide range of processing conditions and a cutting tool using the hard film can be realized. That is, a hard film having excellent wear resistance, heat resistance, defect resistance and excellent film strength can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] [ Figure 1 ] is a longitudinal sectional view schematically showing the surface structure of a cutting tool including a hard coating according to one embodiment of the present invention.
[0020] [ Figure 2 ] is a longitudinal sectional view schematically showing an example of the structure of an arc evaporation device.
[0021] [ Figure 3 ] is observed from above Figure 2 A top view of the arc evaporation device is shown.
[0022] [ Figure 4 ] is an X-ray diffraction pattern obtained by subjecting two cutting tools (sample 1 and sample 2) including hard films stacked with AlCrN and TiSiN to X-ray diffraction.
[0023] [ Figure 5 ]yes Figure 4 An enlarged view of the vicinity of 2θ=34°~40°.
[0024] [ Figure 6 ] is an X-ray diffraction pattern obtained by subjecting three types of cutting tools (Samples 3 to 5) including hard films laminated with AlCrN and TiSiN to X-ray diffraction.
[0025] [ Figure 7 ]yes Figure 6 An enlarged view of the vicinity of 2θ=34°~40°.
[0026] [ Figure 8 ] represents the result of observing the hard film of one of the cutting tools obtained in the example by scanning transmission electron microscopy (STEM).
[0027] [ Fig. 9 ] is observed at a magnification of 1 million times Figure 8 The result obtained is the hard film shown in the left figure. DETAILED DESCRIPTION
[0028] The following description is made about one embodiment of the present invention, but the present invention is not limited thereto. The present invention is not limited to the structures described below, and various changes can be made within the scope indicated in the claims. The embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. In addition, unless otherwise specified in this specification, "A to B" indicating a numerical range means "above A and below B".
[0029] [Embodiment 1: Hard coating]
[0030] A hard film according to one embodiment of the present invention includes Al x Cr 1-x The A layer of N contains Ti 1-y Si y N B layers are alternately stacked, when a combination of the alternately stacked A layers and the B layers is set as the C layer, the thickness of the C layer is 7 nm or more and 18 nm or less, the total thickness of the C layer is 1 μm or more and 6 μm or less, and the thickness of the A layer and the B layer are less than 10 nm. (Here, x is 0.6 or more and 0.7 or less, and y is greater than 0.05 and less than 0.08)
[0031] Figure 1 1 is a longitudinal sectional view schematically showing the surface structure of a cutting tool including a hard coating according to an embodiment of the present invention. In the figure, 11 is a substrate, 12 is a hard coating, and 10 is a cutting tool. Figure 1 In the case where n layers of A are stacked and n layers of B are stacked, the A layers are denoted as A1 to A n , the B layer is represented as B1~B n In the figure, “…” means that the path from A3 to B is omitted. n-1 In addition, Figure 1 , the surface of the substrate 1 is coated with the A layer, and the B layer is stacked on the A layer. However, the present invention is not limited to this. The surface of the substrate 1 may be coated with the B layer, and the A layer may be stacked on the B layer.
[0032] exist Figure 1 In the embodiment, the A layer and the B layer are alternately stacked. The C layer (for example, C1, C2 and C3 in the figure) is a combination of the A layer and the B layer stacked alternately. n) has a thickness of greater than 7 nm and less than 18 nm.
[0033] The so-called "structure in which A layer and B layer are alternately stacked" refers to, for example, a structure in which the surface of A layer is in contact with the surface of B layer, and the surface of B layer facing the surface in contact with the A layer is in contact with the surface of another A layer. That is, it refers to a stacked structure in which a combination of a set of A layer and B layer is a repeating unit. For example, a structure in which the surface of A1 layer in the figure is in contact with the surface of B1 layer in the figure, and the surface of B1 layer not in contact with A1 layer is in contact with A2 layer is repeated.
[0034] As described above, the Al constituting the A layer x Cr 1-x N has the advantage of excellent defect resistance at low temperatures, but has the disadvantage of reducing hardness and strength at high temperatures due to N shedding. 1-y Si y N has the advantages of excellent wear resistance and being suitable for high-speed cutting operations, but has the disadvantage of being hard and brittle.
[0035] By making the C layer a thin layer with a thickness of 7 nm to 18 nm, a hard coating that exhibits only the above advantages and does not exhibit the above disadvantages can be realized. This aspect will be described below.
[0036] By setting the thickness of the C layer to be 7 nm or more and 18 nm or less, in the hard film, in a state where the thin C layer is stacked, one A layer is sandwiched between two B layers. Since one A layer is sandwiched between two B layers, the exposed surface of the A layer is only the side surface. Since the C layer is a thin layer, the thickness of the side surface is extremely thin. As a result, the Al2O3 layer of the A layer is 2.3 nm thick. x Cr 1-x N has N even at high temperature 1-y Si y N prevents shedding.
[0037] In addition, by setting the thickness of the C layer to be 7 nm or more and 18 nm or less, in the hard film, in a state where the thin C layer is stacked, one B layer is sandwiched between two A layers. Since the C layer is a thin layer and one B layer is sandwiched between two A layers, the Ti 1-y Si y The development of defects or cracks of the above-mentioned defects of N is x Cr 1-x N prevents.
[0038] Thus, Al x Cr 1-x N and Ti 1-y Si yThe defects of N are prevented from being manifested. Since the hard coating according to one embodiment of the present invention has a structure in which the C layers that prevent the defects from being manifested are stacked, the hard coating as a whole does not manifest the defects and can only manifest the advantages.
[0039] On the other hand, in the package structure described in Patent Document 1, for example, as described above, regarding the most suitable layer thickness, in the case of Al y Cr 1-y The thickness of the N layer is 75nm to 200nm, preferably 120nm to 170nm. z Si 1-z The thickness of the N layer is 50 nm to 150 nm, preferably 70 nm to 120 nm.
[0040] In this structure, due to the thick layer, it is not possible to fully prevent Al y Cr 1-y The N layer may fall off, or the Ti may not be sufficiently prevented. z Si 1-z The hard material layer described in Patent Document 1 has a plurality of mixed layers, and the mixed layers become layers showing average characteristics of AlCrN and TiSiN, or become layers showing defects of either AlCrN or TiSiN.
[0041] The thickness of the C layer in one embodiment of the present invention is more preferably 9 nm to 17 nm, and further preferably 11 nm to 15 nm. x Cr 1-x N loss and Ti 1-y Si y N is the development of defects or cracks etc.
[0042] In the hard coating according to one embodiment of the present invention, the thickness of each of the A layer and the B layer is less than 10 nm.
[0043] In order for the hard film to exhibit excellent wear resistance, heat resistance, defect resistance, and high film strength, the A layer and the B layer are preferably contained in the C layer in a balanced manner. Therefore, the ratio of the thickness of the A layer to the thickness of the B layer in the C layer is preferably 2:3 to 3:2, more preferably 4:5 to 5:4, and most preferably 6:7.
[0044] The total thickness of the C layer is 1 μm or more and 6 μm or less. That is, the hard coating has a structure in which a very large number of C layers are stacked, that is, a super multilayer structure.
[0045] The hard film is repeatedly capable of only showing Al x Cr 1-x N and Ti 1-y Si y N structure, and a structure formed by stacking super-multilayers. Therefore, the hard film has excellent wear resistance, heat resistance, and defect resistance, and has excellent film strength. Since the hard film has these excellent properties, various materials from soft materials to hard materials (for example, hardness of 20HRC to 60HRC) can be processed, and various processing conditions can be coped with.
[0046] Therefore, high performance can be stably exerted under a wide range of processing conditions. In addition, the various processing conditions include conditions corresponding to processing temperatures ranging from low to high temperatures, conditions corresponding to processing methods such as wet processing, dry processing, and high-speed cutting, etc.
[0047] Among them, the hard film can be preferably used for gear cutting. Gear cutting is a process of making steel or the like into a complex gear shape. The processing of the gear shape with a large cutout applies a large load to the cutting tool blade. In addition, the processing of the gear shape with a small cutout applies a load only to the cutting tool tip. Therefore, the hard film used for gear cutting is particularly required to have wear resistance, heat resistance, defect resistance and high strength.
[0048] In a hard film with any one of weak wear resistance, heat resistance, defect resistance and strength, the weak part cannot withstand the harsh cutting conditions, thus shortening the life of the cutting tool and reducing the processing efficiency. The hard film of one embodiment of the present invention has excellent wear resistance, heat resistance, and defect resistance as described above, and has excellent film strength. Therefore, it can be preferably used for gear cutting. Of course, it is not limited to this, and the hard film can also be preferably used for other processing purposes. For example, it can also be preferably used as a hard film of a superhard alloy blade, a drill, an end mill, etc. described later.
[0049] The total thickness of the C layer is more preferably 2 μm or more and 4.5 μm or less.
[0050] The hard coating may be in a form where the A layer without forming the C layer is laminated on the B layer with the C layer formed at the end of the laminated structure. Figure 1 B shown n Similarly, the hard coating may be in a form in which a layer B, which does not form the C layer, is laminated next to the layer A, which forms the C layer, at the end of the laminated structure.
[0051] In this case, the structure in which the A layer is sandwiched between two B layers or the structure in which the B layer is sandwiched between two A layers is formed. Therefore, similarly to the case in which an integer number of C layers are stacked, only Al x Cr 1-x N and Ti 1-y Si y The advantages of N.
[0052] The Al x Cr 1-x The x of N is 0.6 or more and 0.7 or less, and the Ti 1-y Si y The above-mentioned y of N is more than 0.05 and less than 0.08. The composition of the hard film according to one embodiment of the present invention contains Al x Cr 1-x N A layer and Ti 1-y Si y The B layer of N satisfies the necessary conditions that the thickness of the C layer is 7 nm to 18 nm, and the total thickness of the C layer is 1 μm to 6 μm. Thus, the hard film can exhibit the excellent wear resistance and the like.
[0053] The x is 0.6 or more and 0.7 or less. x Cr 1-x N can be prepared by controlling the composition of the AlCr target material as a raw material, the pressure of N2 during the formation of the C layer, the bias voltage, etc. 1-y Si y N can also be prepared by controlling the composition of the TiSi target material as a raw material, the pressure of N2 during the formation of the C layer, the bias voltage, etc.
[0054] In addition, the prepared Al can be confirmed by an energy dispersive X-ray (EDX) analyzer attached to a scanning electron microscope (SEM) and / or a transmission electron microscope (TEM). x Cr 1-x N has x of 0.6 or more and 0.7 or less, and Ti 1-y Si y y of N exceeds 0.05 and is less than 0.08.
[0055] The hard coating of one embodiment of the present invention can be manufactured, for example, by applying arc ion plating to a substrate. As an apparatus that can be used in the method, for example, a vacuum film forming apparatus such as an arc evaporation apparatus (manufactured by ITF Co., Ltd., Japan) including a single-control (steer one) evaporation source can be cited.
[0056] Figure 2 It is a longitudinal sectional view schematically showing an example of the structure of the arc evaporation device. Figure 3 Observed from above Figure 2 The top view of the arc evaporation device shown in FIG. 20 is the arc evaporation device, 21 is the Cr evaporation source, and 22 is the Al x Cr 1-x Arc evaporation source, 23 is Ti 1-y Si y 2 is an arc evaporation source, 24 is a rotating table, 25 is a small table, 26 is an arc power supply, and 27 is a bias power supply. The small table 25 is connected to the rotating table 24 through gears, and thus rotates by the rotation of the rotating table 24. When the number of gears of the small table 25 is set to 1, the gear ratio of the rotating table 24 to the small table 25 is preferably a value greater than 6 and not an integer.
[0057] The interior of the arc evaporation device 20 is a vacuum chamber. Hereinafter, an example of a method for manufacturing a cutting tool by coating a substrate with a hard film according to an embodiment of the present invention using the arc evaporation device 20 will be described. This method is also used in the examples described below.
[0058] First, the rotary table 24 in which the substrate 11 is placed on the small table 25 is installed inside the arc evaporation device 20 (inside the furnace).
[0059] Next, the interior of the arc evaporation device 20 is set to a predetermined vacuum degree, and the substrate 11 is heated by a heater (not shown) until the substrate 11 reaches 400° C. Figure 3 As shown in FIG. 1 , argon gas is introduced into the furnace, and the pressure in the furnace is set to 1 Pa. Then, a bias voltage of -900 V is applied to the substrate 11 by the bias power supply 27, and the substrate 11 is etched by argon ions. After the argon gas is exhausted, as shown in FIG. Figure 3 As shown, nitrogen gas was introduced into the furnace, and the internal pressure was set to 4Pa.
[0060] Next, the arc power source 26 was operated to generate an arc evaporation source 22 at 150 A to deposit Al. x Cr 1-x Arc discharge is performed, and Ti is evaporated at 140A from the arc evaporation source 23. 1-y Si yArc discharge is performed. x Cr 1-x and Ti 1-y Si y Evaporate under nitrogen atmosphere.
[0061] The rotating table 24 rotates and the substrate 11 rotates. Therefore, when the substrate 11 faces the arc evaporation source 22, the Al x Cr 1-x The Al x Cr 1-x The N film is formed on the surface of the substrate 11 .
[0062] On the other hand, when the substrate 11 faces the arc evaporation source 23, Ti 1-y Si y The Ti 1-y Si y The N film is formed on the surface of the substrate 11 .
[0063] By repeating the above-mentioned operations, a hard film according to an embodiment of the present invention can be formed on the surface of the substrate 11. At this time, by applying a bias voltage to the substrate 11, the evaporated metal element (Ti, Si, Al, Cr) ions are strongly introduced into the substrate 11, the film is densified, and the strength and residual stress of the hard film are adjusted.
[0064] By adjusting the arc current and the rotation speed of the rotary table 24 , the thickness of the C layer and the total thickness of the C layer can be controlled to be greater than 7 nm and less than 18 nm and greater than 1 μm and less than 6 μm, respectively.
[0065] After forming the hard film having a predetermined C layer thickness and a total C layer thickness, the furnace is cooled until the temperature in the furnace becomes 200° C. or less, the atmosphere in the furnace is released, and the manufactured cutting tool is taken out.
[0066] The manufactured hard film can be confirmed to have a predetermined structure by observing the longitudinal section of the hard film, for example, using a scanning transmission electron microscope. The predetermined structure is a structure in which the thickness of the C layer including the structure in which the A layer and the B layer are alternately stacked is 7 nm or more and 18 nm or less, and the total thickness of the C layer is 1 μm or more and 6 μm or less. For example, based on the following Fig. 9 The observation results shown in the figure are as follows: the total thickness of 10 to 20 layers is measured and divided by the number of combinations of layer A and layer B, thereby calculating the thickness of layer C. The thickness of layer A and layer B can be obtained by measuring the thickness of each layer of about 5 to 10 layers and calculating the average value.
[0067] In the hard coating according to one embodiment of the present invention, in the X-ray diffraction pattern of the hard coating, the ratio (A / B) of the intensity of the sub-peak (A) to the intensity of the main peak (B) is preferably 0.4 or more and 0.75 or less.
[0068] The main peak is a peak of the crystals of the A layer and the B layer. The sub-peak is a peak that appears near the main peak (near the low-angle side and the high-angle side of the main peak in the X-ray diffraction pattern) and is a peak caused by the super multi-layer structure. The ratio is an indicator that the hard film includes the super multi-layer structure.
[0069] The X-ray diffraction pattern can be obtained, for example, by measuring the X-ray diffraction of the hard film using the θ-2θ method under the following conditions. The conditions are: measuring device: X-ray diffraction device D8 DISCOVER manufactured by Bruker AXS, X-ray source: Cu-Kα, tube voltage: 40 kV, tube current: 40 mA, slit width: 0.5°, one-dimensional detector, step size: 0.02°, accumulation time: 0.6 seconds, scanning range 2θ=30°~50°. The method for determining the ratio (A / B) is described below.
[0070] Figure 4 These are X-ray diffraction patterns obtained by subjecting two types of cutting tools (Sample 1 and Sample 2) including hard films laminated with AlCrN and TiSiN to X-ray diffraction. Figure 5 yes Figure 4 An enlarged view of the vicinity of 2θ=34°~40°.
[0071] First, if Figure 5 As shown, for each of Sample 1 and Sample 2, a straight line is drawn to connect the intensity at 2θ=34° and the intensity at 2θ=39°. Next, the difference between each of the sub-peak 1 near 36°, the peak of the TiSiN(111) surface near 36.5°, the peak of the AlCrN(111) surface near 37.3°, and the sub-peak 2 near 37.8° and the straight line (the length of the vertical straight line shown in the figure) is set as the intensity I1, I2, I3, and I4 of each peak. And (I1+I4) / (I2+I3) is set as the ratio (A / B). For Figure 4 Table 1 shows the results of determining the above ratios for Sample 1 and Sample 2.
[0072] [Table 1]
[0073] Sample 1 Sample 2 I1 (intensity of sub-peak 1) 238 330 I2 (peak intensity of TiSiN(111) surface) 656 696 I3 (peak intensity of AlCrN(111) surface) 678 992 I4 (intensity of sub-peak 2) 463 817 (I1+I4) / (I2+I3) 0.525 0.680
[0074] Figure 6These are X-ray diffraction patterns obtained by subjecting three types of cutting tools (Samples 3 to 5) including hard films laminated with AlCrN and TiSiN to X-ray diffraction. Figure 7 yes Figure 6 The enlarged view of the vicinity of 2θ = 34° to 40°. Figure 7 The ratio (A / B) was determined by the same method as described for Sample 1 and Sample 2. The results are shown in Table 2.
[0075] [Table 2]
[0076] Sample 3 Sample 4 Sample 5 I1 (intensity of sub-peak 1) unknown 90 170 I2 (peak intensity of TiSiN(111) surface) 90 209 521 I3 (peak intensity of AlCrN(111) surface) 92 249 518 I4 (intensity of sub-peak 2) 65 270 662 (I1+I4) / (I2+I3) 0.357 0.786 0.801
[0077] The ratio is more preferably 0.45 or more and 0.72 or less, and further preferably 0.5 or more and 0.55 or less. This can be used as a more useful indicator that the hard film includes the super multilayer structure.
[0078] The hard film of one embodiment of the present invention preferably has a compressive stress of not less than -0.5 GPa and not more than -4.0 GPa. According to the structure, the hard film has strong resistance to impact and is not easily damaged. According to the viewpoint, the compressive stress is more preferably not less than -1 GPa and not more than -3 GPa, and further preferably not less than -1.5 GPa and not more than -2.5 GPa. The compressive stress can be measured, for example, by using sinusoidal X-ray diffraction. 2 The φ method or the measurement method based on the Stoney equation using a test piece is used for measurement.
[0079] The surface roughness Ra of the hard film of one embodiment of the present invention is preferably 0.03 μm or more and 0.18 μm or less. If the surface roughness Ra exceeds 0.18 μm, not only the surface of the hard film but also the inside will be uneven, and it is not easy to form the super multilayer structure. In addition, it is not easy to find the sub-peak in the X-ray diffraction pattern. The lower the lower limit of the surface roughness Ra, the better, and the actual lower limit is 0.03 μm.
[0080] Therefore, the fact that the surface roughness Ra of the hard film is 0.03 μm or more and 0.18 μm or less is an indicator that the hard film of one embodiment of the present invention has the super multilayer structure. In addition, according to the structure, it can be said that the surface smoothness of the hard film is very high.
[0081] Thus, the hard film can stably exhibit high performance under a wide range of processing conditions and has high smoothness, thereby improving the quality of the processed object.
[0082] From this viewpoint, the surface roughness Ra of the hard film is more preferably 0.06 μm or more and 0.15 μm or less, and further preferably 0.08 μm or more and 0.14 μm or less.
[0083] The surface roughness Ra can be measured, for example, by the following method: that is, a method in which the surface of a test piece having a sufficiently small surface roughness Ra is coated with the hard coating using an ion plating method or the like, and the surface roughness Ra of the coated test piece is measured.
[0084] The test piece may have a surface roughness Ra of 0.01 μm or less, for example. Since the surface roughness Ra of the test piece is sufficiently small, the surface roughness Ra of the test piece coated with the hard film may be regarded as the surface roughness Ra of the hard film.
[0085] In addition, as other methods for measuring the surface roughness Ra, for example, the following method can be cited. That is, for a cutting tool whose surface is coated by an ion plating method or the like, a longitudinal section is made. Then, the shape of the interface between the hard film and the substrate is taken out as the profile of the substrate surface by a scanning electron microscope, and Ra is calculated according to the Ra calculation method. Similarly, the shape of the hard film surface is taken out as the film surface profile, and Ra is calculated according to the Ra calculation method. The value obtained by subtracting the Ra of the substrate surface from the Ra of the film surface is taken as the Ra of the hard film.
[0086] In addition, the measurement of Ra can be performed using, for example, a surface roughness measuring machine manufactured by DEKTAK.
[0087] The hard film according to one embodiment of the present invention preferably has a nanoindentation hardness of 35 GPa or more and 40 GPa or less.
[0088] According to the above structure, the hard film has sufficient strength and thus has sufficient resistance even to processing of materials with high hardness, thereby contributing to improving the sharpness of the cutting tool and improving the discharge performance of chips.
[0089] The nanoindentation hardness can be measured, for example, by using a nanoindenter ENT-1100 manufactured by Elionix Corporation as a measuring device and applying a load of 2 g to a hard film formed on the surface of a cutting tool using a Berkovich indenter.
[0090] [Implementation 2: Cutting tool]
[0091] A cutting tool according to an embodiment of the present invention includes a substrate and a hard coating covering a surface of the substrate, and the hard coating is the hard coating according to an embodiment of the present invention.
[0092] Examples of the cutting tools include gear cutting tools such as hobs, carbide blades, broaches, rolling dies, shaving cutters, and pinion milling cutters; drills; end mills; thread cutting tools such as taps, thread dies, thread cutters, thread milling cutters, and thread rolling dies; tool tip replacement tools such as insert tools; and wear-resistant tools such as drawing tools, rolling tools, shearing tools, forging tools, dies, tools for electronic-related parts, and mechanical mounting parts.
[0093] The hard coating of one embodiment of the present invention has not only one of wear resistance, heat resistance, defect resistance and high hardness, but also all of these characteristics in a balanced manner. Therefore, the cutting tool can cope with a wide range of workpiece materials with a hardness of 20HRC to 60HRC, for example.
[0094] In recent years, high-speed machining and dry machining have been developing, and the use conditions of gear cutting tools have tended to increase the impact on the cutting edge and increase the cutting edge temperature. In addition, gear cutting tools, such as hobs, have multiple cutting edges, but due to the characteristics of gear cutting processing, the load applied to the cutting edge varies for each cutting edge.
[0095] Therefore, a cutting tool including a hard coating having any one of the above characteristics being weak cannot be used stably under the above conditions of use. In addition, the cutting tool cannot cope with loads that change for each cutting edge, and thus cannot be used as a gear cutting tool. The cutting tool of one embodiment of the present invention has all of the above characteristics in a balanced manner, and thus can operate stably even under the above conditions of use. In addition, it can be preferably used as a gear cutting tool.
[0096] The cutting tool can be obtained by forming the hard film on the substrate by arc ion plating or the like. As other methods, sputtering methods such as high-power impulse magnetron sputtering (HiPIMS) or vapor deposition methods can also be used.
[0097] As the substrate, high speed steel, superhard alloy, etc. can be used. As the superhard alloy, WC-Co alloy, WC-TiC-Co alloy, WC-TaC-Co alloy, WC-TiC-TaC-Co alloy, WC-Ni alloy, WC-Ni-Cr alloy, etc. can be used.
[0098] 〔Summarize〕
[0099] The present invention includes the following embodiments.
[0100] <1>
[0101] A hard film comprising Al x Cr 1-x The A layer of N contains Ti 1-y Si y The structure of N B layers stacked alternately,
[0102] When a combination of the A layer and the B layer stacked alternately is defined as a C layer, the thickness of the C layer is 7 nm or more and 18 nm or less,
[0103] The total thickness of the C layer is 1 μm or more and 6 μm or less,
[0104] The thickness of the A layer and the B layer is less than 10 nm respectively.
[0105] (Here, x is greater than or equal to 0.6 and less than or equal to 0.7, and y is greater than 0.05 and less than 0.08)
[0106] <2>
[0107] The hard coating according to <1>, wherein in an X-ray diffraction pattern of the hard coating, a ratio (A / B) of the intensity of a sub-peak (A) to the intensity of a main peak (B) is 0.4 or more and 0.75 or less.
[0108] <3>
[0109] The hard coating according to <1> or <2>, wherein the compressive stress is -0.5 GPa or more and -4.0 GPa or less.
[0110] <4>
[0111] The hard coating according to any one of <1> to <3>, wherein the surface roughness Ra is 0.03 μm or more and 0.18 μm or less.
[0112] <5>
[0113] A cutting tool comprising: a substrate and a hard coating covering a surface of the substrate, wherein the hard coating is the hard coating according to any one of <1> to <4>.
[0114] <6>
[0115] The cutting tool according to <5>, wherein the cutting tool is a gear cutting tool.
[0116] The present invention is not limited to the above-described embodiments, and various modifications can be made within the scope of the claims. Embodiments obtained by appropriately combining technical means disclosed in different embodiments are also included in the technical scope of the present invention.
[0117] Example
[0118] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.
[0119] [Example 1 to Example 13]
[0120] (1) Production of a Cutting Tool Having a Hard Coating According to an Embodiment of the Present Invention
[0121] use Figure 2 and Figure 3 The arc evaporation device 20 shown in FIG. Figure 2 and Figure 3 Based on the method, a cutting tool including a hard coating according to an embodiment of the present invention was manufactured. As substrates, a high-speed steel hob; a 20 mm square, 2 mm thick high-speed steel test piece (surface roughness Ra = 0.01 μm or less) with a mirror-polished surface; and a super-hard alloy test piece with a width of 10 mm, a length of 20 mm, and a thickness of 1 mm were used. In this embodiment, a total of 13 hobs with a diameter of 80 mm and a length of 150 mm were manufactured. They were used as cutting tools for Examples 1 to 13.
[0122] When preparing the cutting tools of Examples 1 to 13, the Al x Cr 1-x The x of each is 0.6 or more and 0.7 or less (the "Al composition" column in Table 3). 1-y Si y The y of each of them is greater than 0.05 and less than 0.08 (the "Si composition" column in Table 3). x Cr 1-x The composition ratio (atm%) of Al and Cr in the N layer and the B layer (containing Ti 1-y Si y The composition ratio (atm%) of Ti and Si in the layer of N) is shown in Table 3. In addition, the thickness of the C layer, the film thickness of the hard film (the total thickness of the C layer), and the number of layers (the sum of the number of layers of the A layer and the number of layers of the B layer) are also shown in Table 3.
[0123] For each embodiment, the high-speed steel test piece and the super-hard alloy test piece are also provided to the method at the same time as each embodiment. The atm% of the hard film formed on these test pieces, the thickness of the C layer, the total thickness of the C layer, and the number of layers are the same as those of the hard film obtained in the corresponding embodiment.
[0124] Figure 8The following is a result of observing a longitudinal section of a hard coating of one of the cutting tools obtained in Examples using a scanning transmission electron microscope (STEM) (bright field image; magnification: 50,000 times).
[0125] Fig. 9 Observed at a magnification of 1 million times Figure 8 The results obtained for the hard film shown in FIG. Fig. 9 As shown, it can be seen that a regular stacking structure is well formed. Fig. 9 The thickness of the C layer can be calculated by measuring the total thickness of 10 to 20 consecutive layers based on the observation results of STEM and dividing it by the number of combinations of the A layer and the B layer. For the hard coatings obtained in Examples 1 to 13 and Comparative Examples 1 to 4, the thickness of the C layer was calculated based on the observation results by STEM. The total thickness of the C layer was obtained by measuring the total thickness of the C layer observed by the STEM.
[0126] (2) X-ray diffraction
[0127] The rollers obtained in Examples 1 to 13 were subjected to X-ray diffraction and measured using the θ-2θ method under the following conditions. The conditions are: measuring device: X-ray diffraction device D8 DISCOVER manufactured by Bruker AXS, X-ray source: Cu-Kα, tube voltage: 40 kV, tube current: 40 mA, slit width: 0.5°, step length: 0.02°, accumulation time: 0.6 seconds, scanning range 2θ = 30° to 50°. Next, based on the X-ray diffraction pattern obtained for each roller, the reference Figure 3 to Figure 6 The above method was performed to determine the ratio (A / B) of the intensity of the sub-peak (A) to the intensity of the main peak (B). The results are shown in Table 3.
[0128] (3) Measurement of surface roughness Ra of hard coating
[0129] The surface roughness Ra of the surface-coated test pieces made of high-speed steel obtained simultaneously with Examples 1 to 13 was measured using a surface roughness measuring machine manufactured by DEKTAK as the surface roughness Ra of the hard film.
[0130] (4) Measurement of nanoindentation hardness of hard coating
[0131] The nanoindentation hardness of the hard film on the surface of each cutting tool was measured using a nanoindenter ENT-1100 manufactured by Elionix Corporation and a Berkovich indenter at a load of 2 g. The results are shown in Table 3.
[0132] (5) Determination of compressive stress
[0133] The surface-coated test pieces made of cemented carbide obtained in Examples 1 to 13 were measured for warpage using a surface roughness measuring machine manufactured by DEKTAK, and for compressive stress based on the Stoney equation.
[0134] (6) Cutting test 1
[0135] The hobs obtained in Examples 1 to 7 were used for dry machining of SCM415 gears under the conditions of cutting speed (V) = 180 m / min, feed 2.5 mm / rev., and down milling. The wear width of the tool tip was confirmed under a microscope after every 100 machining. The results were evaluated based on the number of machinings until the wear width exceeded 0.2 mm or the tool tip was damaged. The results are shown in Table 3.
[0136] (7) Cutting test 2
[0137] The hobs obtained in Examples 8 to 13 were used for dry machining of gears made of SCR420H under the conditions of cutting speed (V) = 160 m / min, feed 1.5 mm / rev., and down milling. The wear width of the tool tip was confirmed under a microscope after every 100 machining. The results were evaluated based on the number of machinings until the wear width exceeded 0.2 mm or the tool tip was damaged. The results are shown in Table 3.
[0138] [Comparative Example 1 to Comparative Example 4]
[0139] By the same method as in Examples 1 to 13, a high-speed steel hob, a 20 mm square high-speed steel test piece with a mirror-polished surface and a thickness of 2 mm, and a super-hard alloy test piece with a width of 10 mm, a length of 20 mm, and a thickness of 1 mm were formed with an A layer and a B layer having the composition shown in Table 3. As a result, a hob and a test piece were obtained in which the thickness of the C layer, the total thickness of the C layer, and the number of layers were set to the values shown in Table 3.
[0140] When the cutting tools of Comparative Examples 1 to 4 were prepared, Al x Cr 1-xThe x of each is the value described in the "Al composition" column of Table 3. 1-y Si y y are the values recorded in the "Si composition" column of Table 3. In Comparative Examples 3 and 4, compared with Examples 1 to 13 and Comparative Examples 1 and 2, the arc current and the rotation speed of the rotary table 25 are changed to make the C layer thickness less than 7 nm or more than 18 nm.
[0141] The hob was subjected to X-ray diffraction, measurement of nanoindentation hardness of the hard film, and cutting test 1 in the same manner as in Examples 1 to 13. In addition, the surface roughness Ra was measured using the surface-coated test piece made of the high-speed steel, and the compressive stress was measured using the surface-coated test piece made of the superhard alloy. The results are shown in Table 3.
[0142] [Table 3]
[0143]
[0144]
[0145] The “sub-peak intensity ratio” is the ratio (A / B) of the intensity of the sub-peak (A) to the intensity of the main peak (B) in the X-ray diffraction pattern of the hard film, and the “film hardness” is the nanoindentation hardness of the hard film.
[0146] The Si composition of Comparative Example 1 is 5.0 atm% and not more than 5 atm%. The Si composition of Comparative Example 2 is 8.0 atm% and not less than 8 atm%. The C layer thickness of Comparative Example 3 is 5 nm, and does not meet the necessary condition of being 7 nm or more and 18 nm or less. The C layer thickness of Comparative Example 4 is 20 nm, and does not meet the necessary condition of being 7 nm or more and 18 nm or less.
[0147] The sub-peak intensity ratio and surface roughness Ra of the hobs described in Comparative Examples 1 to 4 were similar to those of the examples, but the result of cutting test 1 was significantly inferior to that of the examples. This is probably because the necessary conditions for the hard coating according to one embodiment of the present invention were not met.
[0148] On the other hand, all the hobs described in Examples 1 to 13 satisfy the Al composition, Cr composition, Ti composition, Si composition, C layer thickness, and total C layer thickness required for the hard coating according to one embodiment of the present invention. As a result, the cutting test results were very good.
[0149] Thus, it can be seen that the hard film according to one embodiment of the present invention satisfies the requirement of "including Al x Cr 1-x The A layer of N contains Ti1-y Si y N and B layers are alternately stacked, when a combination of a group of the alternately stacked A layers and the B layers is set as a C layer, the thickness of the C layer is greater than 7nm and less than 18nm, the total thickness of the C layer is greater than 1μm and less than 6μm, and the thickness of the A layer and the B layer are respectively less than 10nm (here, the x is greater than 0.6 and less than 0.7, and the y is greater than 0.05 and less than 0.08)". A hard coating having excellent wear resistance, heat resistance, defect resistance and excellent film strength can be provided.
[0150] Industrial Applicability
[0151] The present invention can be preferably used for cutting tools used under a wide range of machining conditions.
[0152] Explanation of symbols
[0153] 10: Cutting tools
[0154] 11: Base material
[0155] 12: Hard coating
[0156] A1~A n :A layer
[0157] B1~B n : B layer
[0158] C1~C n : C layer
[0159] 20: Arc evaporation device
[0160] 21: Cr evaporation source
[0161] 22: Al x Cr 1-x Arc evaporation source
[0162] 23: Ti 1-y Si y Arc evaporation source
[0163] 24: Rotating table
[0164] 25: Small workbench
[0165] 26: Arc power supply
[0166] 27: Bias power supply
Claims
1. A hard film comprising Al x Cr 1-x The A layer of N and Ti 1-y Si y The structure of N B layers stacked alternately, When a combination of the A layer and the B layer stacked alternately is defined as a C layer, the thickness of the C layer is 7 nm or more and 18 nm or less, The total thickness of the C layer is 1 μm or more and 6 μm or less, The thickness of the A layer and the B layer are less than 10 nm respectively. (Here, the x is greater than or equal to 0.6 and less than or equal to 0.7, and the y is greater than 0.05 and less than 0.08).
2. The hard film according to claim 1, wherein In the X-ray diffraction pattern of the hard film, a ratio (A / B) of the intensity of the sub-peak (A) to the intensity of the main peak (B) is 0.4 or more and 0.75 or less.
3. The hard film according to claim 1, wherein The compressive stress is -0.5 GPa or more and -4.0 GPa or less.
4. The hard film according to claim 1, wherein The surface roughness Ra is 0.03 μm or more and 0.18 μm or less.
5. A cutting tool comprising: A substrate, and a hard film covering a surface of the substrate, wherein the hard film is the hard film according to any one of claims 1 to 4.
6. The cutting tool according to claim 5, wherein: The cutting tool is a gear cutting tool.
